Treatment Costs for Nasopharyngeal Cancer by Stages : Patients’ Experience in Sarawak General Hospital - Choi Yean, Yeoh; Chin Hong, Puah; Rayenda Khresna, Brahmana; Shirly Wong, Siew Ling; Harry, Entebang (Sciedu Press, 2020)
The study investigates an average direct and indirect costs incurred by Nasopharyngeal Cancer (NPC) patients who received diagnosis, treatment and follow up in the Sarawak General Hospital, Kuching, Malaysia. A total of 299 NPC patients were randomly selected using a primary data collection approach from the Sarawak General Hospital between November 2018-March 2019. Information related to the average direct and indirect costs incurred by NPC patients at various stages and the sources of their financial assistance throughout the treatment periods were assorted. The study reveals that the total average cost of 169 or 56.52% of the NPC patients who received various treatment services in the public hospital is RM13,165 against RM78,860 on 130 or 43.48% of the patients received the same services in both public and private healthcare. Major sources of funding come from patients’ savings, family members, medical insurances, non-profit organization or charity, company healthcare benefits, employees’ provident fund (EPF) as well as subsidy from the government: This study suggests that the treatment cost for cancer patient is high and hence, there is a need to establish a mechanism that can provide a free screening test for NPC as a forward step to cancer prevention, while for policy makers to develop a more supportive initiative to address the needs of the poor patients.